Spätfolgen nach Immuntherapie: Immunvermittelte Nebenwirkungen von Checkpointinhibitoren - Duong, Sophie L.; Zierold, Sarah; Kramer, Rafaela; Reincke, Martin; Kerl-French, Katrin; Boehmerle, Wolfgang; Pavel, Marianne Ellen; Weckbach, Ludwig; French, Lars E.; Knauss, Samuel; Heinzerling, Lucie (Onkologe, 2021)
Background: Immune checkpoint inhibitors (ICIs) are potent immunotherapeutic agents for many tumor entities. However, ICIs can induce immune-related adverse events (irAE) that can potentially affect any organ system, causing life-changing sequelae or even death. These irAEs can occur months after termination of immunotherapy and long-term effects may persist for years after finishing therapy. Due to expanding clinical indications for ICIs including therapy in earlier tumor stages, the risk–benefit analysis needs to take into account these long-term side effects. Objectives: The sequelae of ICI therapy are reviewed and the international online registry Side Effect Registry Immuno-Oncology (SERIO) for the unified collection and characterization of irAEs is introduced. Materials and methods: We analyzed data from SERIO and performed a selective literature search in the databases PubMed, Cochrane Central Register of Controlled Trials and Google Scholar to characterize, analyze and summarize long-term sequelae of irAE induced by ICI therapy. Results: The most commonly observed irAEs with long-term sequelae involve the skin (leucotrichia, melanoma-associated hypopigmentation) and endocrine irAEs (thyroiditis, hypophysitis, adrenalitis and diabetes). While the former is especially stigmatizing, endocrine irAEs usually require long-term hormone substitution. Neurologic and cardiologic irAEs are relatively rare, but they are associated with severe complications leading to increased morbidity and mortality. Conclusions: Until now, prospective data about long-term consequences of irAEs are lacking. The SERIO registry addresses this need as irAEs are collected to enable long-term follow-up and optimized management.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Benefit-risk assessment; Data collection; Hypopigmentation; Neoplasms; Registries